Gender differences in four-year incidence of self-reported and performance-based functional disability: The International Mobility in Aging Study. (May 2019) - Auais, Mohammad; Ahmed, Tamer; Alvarado, Beatriz; Phillips, Susan P.; Rosendaal, Nicole; Curcio, Carmen-Lucia; Fernandes, Juliana; Guralnik, Jack; Zunzunegui, Maria Victoria
Highlights: Women had a higher adjusted incidence of ADL and mobility disability over time. Women have higher incidences of disability in self-reported outcomes measures, but not not necessarly in performance-based measures. Future research should focus on exploring sources of discrepant self-reporting of incident disability between men and women. Abstract: Objectives: To examine differences in incidence of functional disability between older women and men. Methods: 2002 participants (65–74 years) were recruited in 2012 from Canada, Brazil, Colombia, and Albania, and re-assessed in 2016. Three measures of functional disability were used (1) Difficulty in any of five mobility-related Activities of Daily Living (ADL disability); (2) Self-reported difficulty climbing a flight of stairs or walking 400 m (mobility disability); and (3) Poor physical performance. We estimated the adjusted gender-specific incidence risk ratios (IRR) for each outcome in 2016. Results: In 2016, 1506 participants (52% women) were re-examined, 80% of the surviving cohort. Among those not disabled in 2012, seventy-four (12.9%) men developed ADL disability, while 105 (19.2%) developed mobility disability, and 97 (16.1%) developed poor physical performance. For women, numbers were higher 120 (21.4%) developed ADL disability, 117 (26.5%) developed mobility disability, and 140 (23.0%) developed poor physical performance. Compared to men, women had a higher adjusted incidence of self-reported ADL disability (IRR 1.4; 95% CI 1.04–1.88) and mobility disability (IRR 1.4; 95% CI 1.06–1.77), but not of poor physical performance (IRR 1.03; 95% CI 0.88–1.32). Conclusions: Although women have a higher self-reported incidence of ADL and mobility disability than men, there was no significant difference in poor physical performance. Reasons for this discrepancy between self-reported and performance-based measures require further investigation. Understanding gender differences in functional disabilities can provide the basis for interventions to prevent mobility loss and minimize any gender gap.